Smart Veterinary Facilities: Integrating IoT and Data-Driven Facilities Management for Enhanced Animal Health and Welfare - Fadimatu Dauda Muhammad; Sani Inusa Milala (Jurnal Krisnadana, 2026)
The veterinary sector in developing nations like Nigeria faces significant efficiency and welfare challenges due to a continued reliance on traditional management systems. Consequently, this study investigates the impact of integrating the Internet of Things (IoT) and data-driven facility management on animal health and welfare. Adopting a quantitative research design, the study analyzed data from a stratified random sample of 120 veterinarians, facility managers, and animal health officers using structured questionnaires Data were collected using structured questionnaires and analyzed using descriptive and inferential statistics, including Pearson correlation and multiple regression. Results revealed a strong positive correlation between IoT adoption and animal health and welfare (r = 0.762, p < 0.01), and between data-driven facility management and operational efficiency (r = 0.703, p < 0.01). The regression analysis indicated that these two predictors explained 63.4% (R² = 0.634) of the variance in animal welfare outcomes (F (2,117) = 45.326, p < 0.001). Respondents also reported improved disease prevention, reduced animal stress, and enhanced decision-making due to real-time monitoring and data analytics. The study concludes that IoT integration and data-driven management significantly improve animal welfare and operational performance in veterinary facilities. However, challenges such as high implementation costs, poor internet infrastructure, and limited technical expertise must be addressed to achieve wider adoption. The findings provide valuable insight for policymakers, veterinarians, and facility managers aiming to develop smart, sustainable, and welfare-oriented veterinary systems in Nigeria and beyond.